Synthesis and optimization of application of a molecular imprinted sorbent for selective determination of two pyrethroid isomers from biological sample - Omid Reza Heravizadeh (بهداشت و ایمنی کار, 2019)
Introduction: Along with the extensive production and use of various pesticides for controlling pests and enhancing the production of agricultural crops, there is a growing concern about the adverse effects of these toxic materials on human health. Therefore, the development of sensitive, selective, and accurate methods for continuous assessment of pesticides concentration in occupational and environmental fields and comparing them with national and international standards is of great importance. This study was aimed at synthesis and application of molecularly imprinted polymer as a selective sorbent for residue determination of two pyrethroid isomers in biological samples. Material and Methods: The MIP particles were prepared by a non-covalent approach using permethrin as a template, chloroform as progen solvent, methacrylic acid as functional monomer and ethyleneglycol dimethacrylate as cross-linker, at 55 °C for 18 hours in an oil bath. Field emission scanning electron microscopy was used to investigate the morphology and size of polymer particles. Afterward, the critical parameters, which could affect the recognition properties of synthesized MIP, were investigated and optimized under the selected operational ranges for the highest adsorption and recycling yield in solid-phase extraction of permethrin in biological samples Results: using precipitation polymerization technique, uniform and spherical particles with the nano-ranged diameter (less than 21.2 nanometers) were obtained. Under the optimized condition, the designed molecularly imprinted solid-phase extraction (MISPE) technique exhibited great potential for the extraction of pesticide isomers in the real sample. More than 93 % of the recovery obtained from spiked urine samples. The linear calibration curve was obtained from 20-120 μg.L-1 (R2=0.99) and the detection limit was less than 6 ppb for both isomers. The presence of interferences had no effect on the selectivity of the method up to 100-fold. Conclusion: employing the molecular imprinted solid-phase extraction method along with the high-performance liquid chromatography technique resulted in a selective and sensitive approach, suitable for quantitative monitoring of the desired pesticide in complex biological samples.